Tomatoes, land, and hearsay: property and history in Asante in the time of structural adjustment - Berry, S (My University, 1997)
As debate over African economic problems and prospects has shifted from concern with the continent's "agricultural crisis" in the 1980s, to a focus on environmental degradation and sustainable development in the 1990s, the policy wheel has come full circle. In the 1980s, a number of donor agencies and governments argued in the 1980s that African economies* rising foreign debts and chronic budgetary deficits were fuelled in large part by stagnating or declining levels of agricultural production, brought on by African governments' poor choice of policies and excessive intervention in domestic markets and production.1 To reduce their debts and regenerate agricultural production for domestic markets and for export, African governments were advised to adopt structural adjustment packages designed to reduce or eliminate controls on prices, trade and output, cut government spending, and transfer assets and productive activities from the public to the private sector.2 By the end of the decade, as many economies began to show signs of agricultural recovery (arguably due as much to better weather and long-term urban growth as to policy-induced shifts in relative prices)3 and greater macroeconomic stability in the short-term, policymakers' attention shifted to the question of how to promote sustained and equitable economic growth in the long run.4 Focussing particularly on the problem of environmental degradation, some analysts have begun to call for increased regulation of Africans* economic activities, from hunting, herding, and farming, to commercial logging, mining and manufacturing. One recent study, sponsored by the World Bank, proposes "an action plan" of incentive schemes to "create demand" for smaller families and improved agricultural technology-backed up by controls to "eliminat[e] openaccess land tenure conditions" and induce "policy-created artificial scarcity of farmland,.." Others have advocated fences, armed guards and/or closely monitored "buffer zones" to prevent exploitation of protected areas and species.5 Having argued in the 1980s for getting the state out of many areas of economic activity in Africa, donor agencies now apparently want to bring it back in.
African Studies Seminar series. Paper presented 19 May, 1997
Keywords: Ghana. Economic conditions; Africa. Economic conditions. 20th century